THE OBJECTIVIZATION OF THE EMOTIONAL CONCEPTS “INTRIGUE” AND “GUILE” IN FICTION COMMUNICATION (BASED ON THE MATERIAL OF THE DRAMA «INTRIGUE AND LOVE» BY F. SCHILLER) (Proceedings of Southern Federal University. Philology, 2012)
Bulbenko E.S.Keywords: emotional concept, emotional dominant, emotionally categorical situation, communication in fiction.The article is devoted to the method of analysing emotionally categorical situations of concepts objectivization based on the material of fiction communication. The author offers the algorithm of the analysis of similar situations. The analysis of linguistic means of the concepts representations allows differentiating basic characteristics of the concepts under study.